Engineering of a Spider Peptide via Conserved Structure-Function Traits Optimizes Sodium Channel Inhibition In Vitro and Anti-Nociception In Vivo - Hu, H.; Mawlawi, S. E.; Zhao, T.; Deuis, J. R.; Jami, S.; Vetter, I.; Lewis, R. J.; Cardoso, F. C. (Frontiers in Molecular Biosciences, 2021)
Venom peptides are potent and selective modulators of voltage-gated ion channels that regulate neuronal function both in health and in disease. We previously identified the spider venom peptide Tap1a from the Venezuelan tarantula Theraphosa apophysis that targeted multiple voltage-gated sodium and calcium channels in visceral pain pathways and inhibited visceral mechano-sensing neurons contributing to irritable bowel syndrome. In this work, alanine scan and domain activity analysis revealed Tap1a inhibited sodium channels by binding with nanomolar affinity to the voltage-sensor domain II utilising conserved structure-function features characteristic of spider peptides belonging to family NaSpTx1. In order to speed up the development of optimized NaV-targeting peptides with greater inhibitory potency and enhanced in vivo activity, we tested the hypothesis that incorporating residues identified from other optimized NaSpTx1 peptides into Tap1a could also optimize its potency for NaVs. Applying this approach, we designed the optimized peptide Tap1a-OPT exhibiting 18 to 41-fold increased potency for NaV1.1, NaV1.2, NaV1.3, NaV1.6 and NaV1.7 involved in several neurological disorders including acute and chronic pain, motor neuron disease and epilepsy. This enhanced potency arose through a slowed off-rate mechanism. Optimized inhibition of NaV channels observed in vitro translated in vivo, with reversal of nocifensive behaviours in a murine model of NaV-mediated pain also enhanced by Tap1a-OPT compared to Tap1a. Molecular docking studies suggested that improved interactions between the loops 3 and 4, and C-terminal of Tap1a-OPT and the NaV channel voltage-sensor domain II were the main drivers of optimized potency. Overall, the rationally designed peptide Tap1a-OPT displayed new and refined structure-function features which are likely the major contributors to its enhanced therapeutic properties observed in vivo. This work contributes to the rapid engineering and optimization of potent and selective spider peptides multi-targeting NaV channels, and the research into novel drugs to treat neurological diseases.